Clinical profile and outcome of neonates with suspected sepsis form a rural medical college hospital of South India - Iyer, Chandrakala R.; G., Naveen; R., Suma H.; Kumarguru, B. N.; K., Swetha; Janakiraman, . (International Journal of Contemporary Pediatrics, 2017)
Background: Sepsis is an important cause of neonatal mortality and morbidity. Nonspecific and subtle clinical features coupled with expensive, time consuming and unavailable definite laboratory tests challenges its accurate diagnosis in clinical practice. Sepsis is traditionally suspected in neonates based on clinical features, maternal and neonatal risk factors and is treated by empirical antibiotics. These risk factors and clinical features are variable depending on geographical, cultural and socio-economic background. We studied the clinical and bacteriological profile of high risk neonates for sepsis development in our Neonatal Intensive Care Unit (NICU), to make the precise clinical diagnosis and prevent inadvertent use of antibiotics. Methods: A prospective observational study was conducted on 200 neonates with suspected sepsis either by high risk factors and /or clinical features admitted to NICU for a period of nine months. After clinical examination, septic screen including blood culture was done and antibiotics were started as per the NICU protocol. Results: Of the 200 neonates studied, 20.5% had positive blood culture with Coagulase negative staphylococci (CoNS) and contaminants. 89.5% had early onset of sepsis (EOS). Neonatal profile showed 60.5% males, 55% inborn, 37.5% premature, 49.5% low birth weight babies. Maternal profile showed 49.5% Primigravida, 73% aged above 20 years at delivery and 97.5% literates. Outcome of admitted neonates showed, 72% were discharged after improvement, 10.5% died and 17.5% discharged against medical advice. Death due to respiratory distress syndrome was common in preterm and male neonates. Conclusions: EOS was common in our NICU. Blood culture showed more CoNS and contaminants necessitating the need for better blood sampling and hand wash technique.